The Urgency of Amending the Balikpapan City Regulation on License to Open State Land - Rahmatika, Nur Auliya; Safa'at, Muchamad Ali; Hadiyantina, Shinta (Pandecta Research Law Journal, 2024)
Through the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency, the central government has established a national priority program called the Acceleration of Systematic Complete Land Registration (PTSL). The program is a first-time land registration process undertaken synchronously in all parts of Indonesia. The PTSL is a form of legal certainty guaranteed by the central government related to land rights to the citizens. However, as part of its regional authority, Balikpapan City regulated the ownership of a License to Open State Land (IMTN) as one of the requirements for PTSL. In the end, it creates a problem in implementing PTSL in Balikpapan City due to the time-consuming process of IMTN letter registration. Although it is disadvantageous for citizens, the requirement of an IMTN letter is in accordance with the Regional Regulation of Balikpapan City. This research is aimed to determine the legal certainty of land rights registration for Balikpapan City people. The research method used in the research is normative juridical, with a statutory approach. The research data is obtained through a literature study for primary data and obtained by direct research in 2021 for secondary data. The research shows that local regulations of Balikpapan City that require IMTN ownership as a condition for PTSL submission are, in fact, in conflict with the Regulation of the Minister of ATR / BPN. Therefore, to achieve legal certainty related to land management in Balikpapan City, it is necessary to adjust the Regional Regulation of Balikpapan City Number 1 Year 2014 on IMTN.